Dynastic human capital, inequality and intergenerational mobility - Adrian Adermon; Mikael Lindahl; Marten Palme (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the importance of the extended family – the dynasty – for the persistence in inequality across generations. We use data including the entire Swedish population, linking four generations. This data structure enables us to identify parents' siblings and cousins, their spouses, and the spouses' siblings. Using various human capital measures, we show that traditional parent-child estimates of intergenerational persistence miss almost one-third of the persistence found at the dynasty level. To assess the importance of genetic links, we use a sample of adoptees. We then find that the importance of the extended family relative to the parents increases.
Keywords: I24; J62; 330; intergenerational mobility; extended family; dynasty; human capital